Interrelationship between the Concepts in J. Piaget and D. Uznadze’s Theories - Nadareishvili, Vakhtang (Georgian Psychological Journal, 2022)
The article reviews the psychological concepts of ‘centration’, ‘decentration’, ‘subjectification’ and ‘objectification’, developed within the framework of different psychological theories, from the perspective of Set Theory. In particular, it examines the specificity of these phenomena, their place, function and interrelationship within the adaptation process. An emphasis is made on the possibility of using J. Piaget’s theoretical approach for the elaboration of the issues relevant to D. Uznadze’s theory, as well as the possibility of the interpretation of J. Piaget’s concepts and psychological mechanisms from the perspective of Set Theory. An attempt is made to prove the productivity of this approach through viewing resources in both theories as mutually complementary and demonstrating the possibility of a synthetic use of these resources for the analysis of the processes and mechanisms involved in adaptive activity.